Temporal muscle thickness as a preoperative predictor of motor aphasia in Moyamoya disease - Liu, Yang; Gao, Jie; Guo, Gaochao; Cui, Yangguang; Zhu, Lin; Li, Chaoyue; Zhao, Liming (Frontiers in Neurology, 2025)
ObjectivePostoperative motor aphasia is a common complication following left-sided combined revascularization surgery for Moyamoya disease (MMD), yet reliable preoperative predictors remain unavailable. This study evaluates preoperative temporal muscle thickness (TMT), a novel MRI-based parameter, as a predictive biomarker for this complication.MethodsWe retrospectively analyzed 34 adult MMD patients who underwent left-sided combined revascularization between April 2021 and June 2023. Preoperative TMT was measured on axial MRI using multi-planar reformation. Statistical analyses (e.g., t-tests) were used to assess the association between preoperative TMT and the incidence, timing, and duration of postoperative motor aphasia.ResultsExcluding complications such as infarction, postoperative aphasia occurred in 28 of 34 patients (82.35%), predominantly pure motor aphasia (25/34, 73.53%), typically emerging on the third postoperative day with a median duration of 4 days. Patients who developed aphasia had significantly greater mean preoperative TMT than those who did not (7.08 ± 1.00 mm vs. 5.70 ± 0.68 mm, respectively; p = 0.003). Furthermore, greater preoperative TMT showed a positive correlation with a longer duration of postoperative aphasia (r = 0.4907, p = 0.0032).ConclusionOur findings confirm that TMT independently predicts the occurrence and severity of postoperative motor aphasia in MMD patients after left-sided revascularization. This MRI metric enhances risk stratification, guiding surgical planning and patient counseling. Further studies are needed to validate its utility and explore preventive measures.